2022
DOI: 10.52727/2078-256x-2021-17-4-20-27
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipid profile parameters, atherogenic index of plasma, anthropometric parameters with the severity of the COVID-19 course in Novosibirsk women

Abstract: Background: Our study aimed to assess the relationship between the parameters of the lipid profile, atherogenic index of plasma (AIP), anthropometry influence with the severity of the new coronavirus infection COVID-19 in women. Material and methods. The study design was a cross-sectional study. The research included 138 women aged 29–82 years who had undergone a new coronavirus infection COVID-19 at least two months ago. Participants were divided into three groups by severity of infection: mild (n = 61), mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Finally, a research logistic regression analysis showed that a moderate course of COVID-19 among Novosibirsk women is associated with BMI (odds ratio (OR) = 1.090, 95% confidence interval (95% CI) 1.019–1.166, p = 0.012), and a severe course is associated with WC (OR = 1.041, 95% CI 1.001–1.084, p = 0.046), AIP ≥ 0.11 (compared to both mild (OR = 13.824, 95% CI 1.505–126.964, p = 0.02) and moderate (OR = 11.579). 3 …”
Section: Lettermentioning
confidence: 99%
“…Finally, a research logistic regression analysis showed that a moderate course of COVID-19 among Novosibirsk women is associated with BMI (odds ratio (OR) = 1.090, 95% confidence interval (95% CI) 1.019–1.166, p = 0.012), and a severe course is associated with WC (OR = 1.041, 95% CI 1.001–1.084, p = 0.046), AIP ≥ 0.11 (compared to both mild (OR = 13.824, 95% CI 1.505–126.964, p = 0.02) and moderate (OR = 11.579). 3 …”
Section: Lettermentioning
confidence: 99%
“…As a result, a research's logistic regression analysis showed that a moderate course of COVID-19 among Novosibirsk women is associated with BMI (odds ratio (OR) = 1.090, 95% confidence interval (95% CI) 1.019-1.166, p = 0.012), and a severe course is associated with WC (OR = 1.041, 95% CI 1.001-1.084, p = 0.046), compared to both mild (OR = 13.824, 95% CI 1.505-126.964, p = 0.02) and moderate (OR = 11.579). [3] In addition, when calculating AIP, the unit of both triglyceride (TG) and high-density lipoprotein (HDL) levels should be mmol. However, the author used mg/dl units when calculating the AIP value.…”
Section: Letter To the Editormentioning
confidence: 99%